ULTRA–WIDE-FIELD IMAGING AND INTRAVENOUS FUNDUS FLUORESCEIN ANGIOGRAPHY IN INFANTS WITH RETINOPATHY OF PREMATURITY. Issue 12 (December 2020) - Mao, Jianbo; Shao, Yirun; Lao, Jimeng; Yu, Xueting; Chen, Yiqi; Zhang, Caiyun; Li, Hanxiao; Shen, Lijun
Abstract : Purpose: To determine the feasibility of ultra–wide-field imaging and ultra–wide-field intravenous fundus fluorescein angiography (UWF-IV-FFA) in infants with retinopathy of prematurity (ROP) using Optos 200Tx. Methods: We performed Optos 200Tx capturing on 32 premature infants (14 females) and UWF-IV-FFA with Optos 200Tx on 12 of the 32 infants between April 2017 and July 2018 at the affiliated eye hospital of Wenzhou Medical University and analyzed their fundus images. Results: Ultra–wide-field color images were acquired from 32 infants (64 eyes). UWF-IV-FFA was performed successfully in 12 premature infants (24 eyes). No adverse events were observed. The ultra–wide-field Optos 200Tx color images and UWF-IV-FFA images revealed Stages 1, 2, and 3 ROP and aggressive posterior ROP. Conclusion: Ultra–wide-field imaging and intravenous fundus fluorescein angiography using Optos 200Tx are feasible in infants with ROP, which have the potential to screen, diagnose, and follow-up for ROP. Abstract : Ultra–wide-field imaging and ultra–wide-field intravenous fundus fluorescein angiography using Optos 200Tx reveal the characteristics of retinopathy of prematurity at different stages, which have the potential to screen, diagnose, and follow-up for retinopathy of prematurity.